A short book about painting - Marr, Andrew (Quadrille Publishing Ltd, 2017)
In 'A short book about painting', writer and broadcaster Andrew Marr tackles the subjects of inspiration, creativity, politics, beauty and form. How does the artist make good work? What constitutes 'good'? How important is technique - and the imagination? Following a serious stroke in 2013 that left him partially paralysed, Marr struggled with the physical rigours of painting using oils. This led to his wrestling with some of the very fundamental questions about painting as an art form in itself - and to interrogate himself daily about brushstrokes, colour balance, line and texture. Using his own work in progress as examples of failures, and examples of techniques from classical artists right up to the present day, Marr examines how the painter can improve and learn from his or her mistakes.